2015
DOI: 10.1590/1516-3180.2013.7080003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heparanase isoforms and cathepsin B in the plasma of patients with gastrointestinal carcinomas: analytical cross-sectional study

Abstract: CONTEXT AND OBJECTIVE: Heparanase-1 degrades heparan sulfate and has been correlated with tumor progression. Although the isoform heparanase-2 has no catalytic activity, it seems to be important for modulating heparanase-1 activity. Cathepsin B is a proteinase involved in tumor metastasis. The aim of this study was to analyze heparanase isoform expression and cathepsin B activity in plasma samples from patients with gastrointestinal carcinomas, compared with healthy individuals (control group). DESIGN AND SETT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The only known endo-β-D-glucuronidase capable of degrading heparan sulfate chains in mammals is heparanase 1 (HPSE1). HPSE1 is upregulated in many inflammatory diseases including cancer 13 , diabetes 14 , and sepsis 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only known endo-β-D-glucuronidase capable of degrading heparan sulfate chains in mammals is heparanase 1 (HPSE1). HPSE1 is upregulated in many inflammatory diseases including cancer 13 , diabetes 14 , and sepsis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…An antagonistic interaction of the heparanases in cancer have been reviewed recently 24 . Although HPSE2 circulates in the human plasma 13 , interactions between HPSE1 and HPSE2 in endothelial cells has not been investigated. Endothelial cells express HPSE1 in vitro 25,26 and serve as an important local source of HPSE1during inflammation 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of Hpa-2 remains to be elucidated. It has been reported that Hpa-2 is secreted by endothelial cells into the circulation of humans and its levels are closely associated with syndecan-1 and -4 proteoglycans on the cell surface [22] , [95] , [98] . However, transcriptional and posttranscriptional regulation of Hpa-2, especially in respect to endothelial cell biology and disease states associated other than cancer, are incompletely understood and need further investigation – especially in systemic inflammatory syndromes such as sepsis.…”
Section: Role Of Heparanase-2 As An Opposing Regulator Of Heparanase-1mentioning
confidence: 99%
“…Furthermore, heparanase is capable of digesting heparan sulfate in the extracellular matrix (ECM), thereby allowing cell invasion (1,2). Increased expression of heparanase is closely related to poor prognosis in several pathological conditions, such as the process of tumor development, epithelial-mesenchymal transition, in ammation, and angiogenesis (3)(4)(5)(6)(7)(8)(9)(10). Higher levels of heparanase expression and enzymatic activity are frequently used as a marker for diagnosis and prognosis of malignant tumors (7,11).…”
Section: Introductionmentioning
confidence: 99%